2017
DOI: 10.1002/er.3895
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity analysis for an ADS system using different nuclear data libraries

Abstract: SummaryThe aim is to update the evaluated nuclear data library (ENDL) for nuclides used to simulate accelerator driven systems with JEFF3.1, JEFF3.2, and ENDF/B-VII.1. The applied methodology was, first of all, reproduced to 3 ENDL comparing the cross sections with the ADS Nuclear Data Library at 293.6 K. Second, libraries were processed at working temperature at 1200 K in containing fissile/fissionable material and 900 K for the remaining regions. Third, it is performed a criticality calculation at steady sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Thus, it is intended to vary the values of L (width) and d (diameter) of the target, as it is expected to estimate the optimal target sizes as a function of the number of neutrons escaping from it. Studies have shown that the number of neutrons escaping from the target increases with increasing target radius and reaches a maximum, after which it decreases with increasing target radius [17].…”
Section: Target Diameter and Widthmentioning
confidence: 99%
“…Thus, it is intended to vary the values of L (width) and d (diameter) of the target, as it is expected to estimate the optimal target sizes as a function of the number of neutrons escaping from it. Studies have shown that the number of neutrons escaping from the target increases with increasing target radius and reaches a maximum, after which it decreases with increasing target radius [17].…”
Section: Target Diameter and Widthmentioning
confidence: 99%
“…Sensitivity analysis for the system can assess the importance of numerous parameters to the system responses for all possible situations. Analysis results can provide useful information to reactor design optimization, uncertainty propagation and quantification, and estimating biases of the simulation code and uncertainty, for instance. Especially for MSR, the influence from the coupled physics such as reactivity feedback from temperature or density changes of moving fuel salt is the issue to assess how much sensitive the system response is.…”
Section: Introductionmentioning
confidence: 99%